(untitled) (Fractal: Journal of Psychology, 2009)
Following further demands, the Psychology Undergraduate Program, at PUC-Minas campus Poços de Caldas, established new possibilities for action and intervention, breaking traditional barriers of clinical work and going toward a conception of "extended-clinic" through the psychological service. This paper intends to describe the dissident experience of serving the population at a psychological service format in a Reference Center for Social Welfare (CRAS), in the municipality of Poços de Caldas. The experience gave the students the opportunity to deal with some challenges to articulate new strategies at unusual areas of the psychologist’s practice, as well as the production of knowledge about these practices.